Photoinhibition and continuous growth of the wild-type and a high-light tolerant strain of Chlamydomonas reinhardtii - Virtanen O; Valev D; Kruse O; Wobbe L; Tyystjärvi E (Academy of Sciences of the Czech Republic, Institute of Experimental Botany, 2022)
The volumetric productivity of the high-light tolerant strain hit2 of Chlamydomonas reinhardtii was found to be higher than that of the parental strain CC124 during continuous growth at PPFD from 200 to 1,500 mu mol m(-2) s(-1). At PPFD of 1,250 mu mol m(-2) s(-1), hit2 produced 2.53 +/- 0.18 and CC124 produced 2.05 +/- 0.12 g(biomass) dm(-3) d(-1). The rate constant of photoinhibition of hit2 was less than half of that of CC124, suggesting that hit2 produces more biomass than CC124 because hit2 does not need to allocate as much resources for PSII repair as CC124. Growth in high light triggered similar loss of chlorophyll, increase in the carotenoid-to-chlorophyll ratio, and decrease in PSI fluorescence in both strains. Thermoluminescence B band was shifted toward the Q band in hit2, suggesting that low redox potential of the Q(B)/Q(B)(-) pair contributes to the photoinhibition tolerance of hit2.